The Great "Dominion": A Pamphlet written by an English Working Man, 30 June 1885, [by] R. James - James, R. (Labour / Le Travail, 1991)
Reproduces the text of a handwritten 1885 opinion piece by R. James that was intended as a pamphlet. In addressing labourers in the British Isles, the writer, himself an English emigrant, cautions that Canada is already "a land of labourers." He accuses the Canadian government of having "turned its back" on labourers during a recent economic downturn, as a result of which they face harsh living and working conditions. Problems of unemployment, job competition, low wages, continental climate, mobility, clothing, food, religion, and ethnicity are described and commented upon. Concludes that if British labourers do book passage, it should be to Western rather than Eastern Canada. The manuscript, the opening page of which is also reproduced, is taken from a document found amongst the pages of the British Association for the Advancement of Science, Annual Meeting, Montreal 1884, Scrapbook I, and is kept at the Blacker-Wood Library, McGill University.
Keywords: GREAT Dominion: A Pamphlet Written by an English Working Man June 30, 1884, The (Book); RAMSEY, Ellen L.